Climate change in the Himalayan region: susceptible impacts on environment and human settlements - Matta, Gagan; Kumar, Amit; Singh Tomar, Dharmendra; Kumar, Rupesh (Frontiers in Environmental Science, 2025)
The Himalayan region, home to the world’s highest mountain ranges, is an ecological and cultural hotspot crucial for the livelihood of nearly two billion people downstream. However, it faces significant vulnerabilities due to climate change, which threatens its fragile ecosystems and socio-economic frameworks. Notably, environmental risks include glacier retreat, biodiversity loss, and shifting water supplies, with adverse consequences for water availability and agricultural productivity. These climatic shifts exacerbate social and economic pressures, disrupting agro-based livelihoods, damaging infrastructure, and intensifying the frequency and severity of extreme weather events. This study highlights the urgent need for region-specific, sustainable development policies that integrate improved climate monitoring, ecosystem-based adaptation, and the synergy between indigenous knowledge and scientific advancements. A comprehensive framework is proposed to safeguard both ecological and socio-economic resilience in the face of ongoing climate change challenges in the Himalayas.